The Characteristic of Lada Powder wrapping with various of packaging (biodegradable film of composite film from Sodium CarboxymethylCellulose which syntesized from Pineapple crown, Biodegradable film of Commercial Sodium CarboxymethylCellulose, and Plastics) during storages - Susana, Susana; Mangunsong, Lamria; Iskandar, Dodi; Purwandani, Ledy (Journal of Food and Pharmaceutical Sciences, 2018)
ABSTRACTThis study aimed to evaluate the use of the composite film Sodium Carboxymethyl Cellulose on the crown of the pineapple to volatile substances of Lada powder, include piperin content (HPLC), Steps being taken in this research is the manufacture of composite films NaCMC and application in Lada powder. The stages in this research are cellulose extraction step and cellulose modification into CMC, making and characterizing composite film as spice packing and its application as spice packer. Cellulose extraction from pineapple crown with 12% NaOH and carboxymethylation with sodium monocloroacetate. Films of sodium carboxymethylcellulose, polyethylene glycol 400 as plasticizer and emulsifier and coconut oil as hydrophobic component to obtain composite film as a spice packing with mechanical properties such as seal strength, thickness, WVTR and solubility in hot water suitable for application as spice packing with thickness 0.085mm) and 350ÂºC sealing temperature variations. The result of the study of carboxymethyl group of pineapple crown CMC synthesis with HPLC showed that plastic packaging is best compared to using CMC comercial and pineapple crown to lada powder wrapping.